Work this farm! - Steele, Michael Anthony; Primeau, Chuck (New York : Scholastic, 2011)
"It's a busy day on the farm! The farmers feed the animals and harvest the crops. A big farm needs big machines!"--P. [4] of cover.
640
Accelerated Reader AR
Keywords: Farms -- Juvenile fiction; LEGO toys -- Juvenile fiction; LEGO toys -- Fiction; Farms -- Fiction